SARS-CoV-2 infection in children, clinical characteristics, diagnostic findings and therapeutic interventions at a tertiary care center in Riyadh, Saudi Arabia. Issue 4 (April 2021) - Alharbi, Musaed; Kazzaz, Yasser M.; Hameed, Tahir; Alqanatish, Jubran; Alkhalaf, Hamad; Alsadoon, Alaa; Alayed, Maria; Hussien, Shahad Abu; Shaalan, Mohammed Al; Al Johani, Sameera M.
Abstract: Background: Coronavirus disease 2019 (COVID-19) pandemic caused by SARS-CoV-2 was first identified in Wuhan, China. All ages are susceptible to SARS-CoV-2 infection. Few studies had reported milder course in children however, severe course of illness has been reported. We aimed to describe the clinical features of COVID-19 in pediatric patients including diagnostic findings and therapeutic interventions in sever disease manifestation. Methods: We retrospectively reviewed 742 patients with SARS-CoV-2 proven infection at King Abdullah Specialist Children's Hospital, from April 2020 and July 2020. Inpatients, outpatient, including those with sever manifestation treated at the Intensive Care Unit (ICU) were included. We collected data including demographic data, comorbidities, symptoms, imaging data, laboratory findings, treatments and clinical outcomes of patients with COVID-19. Results: Among of 742 patients, 71 (9.6%) were hospitalized. The median age of patients was 75 months old and 53.6 were male. A total of 461 (62.1%) had close contact with confirmed cases, 45 (6.1%) had no contact history, and 236 (31.8%) with unknown exposure risk. The most common symptoms at the onset of illness were fever (32.5%), respiratory symptoms (21%) and gastrointestinal symptoms (10.3%). Among the entire cohort, 7 patients were admitted to PICU with COVID-19 related symptoms, five patients diagnosed with MIS-C, one patient with Kawasaki, and one patient with pneumonia. All patients received supportive therapy, no antiviral treatment had been used however, in MIS-C patients IVIG had been given to all patients, five patients received Anakinra; and one patient received tocilizumab. Conclusions: In this study, children infected with SARS-CoV-2 are less likely to develop symptomatic or serious diseases. Among symptomatic children, the most common clinical features were fever and respiratory symptoms followed by gastrointestinal manifestations. The majority of infected children have reported contact with an infected individual. MIS-C associated with COVID-19 is a severe presentation of SARS-CoV-2 infection and of a major concern as an overlapping features with other diseases could happen, making the diagnosis challenging.